Trends of Proton Pump Inhibitor Uses among Pharmaceutical Promotional Workers - Saha, Shasanka Kumar; Saha, Madhusudan; Shil, Bimal Chandra; Saifullah, Md ANM; Hasan, Monirul; Chowdhury, Nahian Faruque (Sir Salimullah Medical College Journal, 2023)
Background: Proton pump inhibitors (PPIs) are one of the most frequently used drugs in the world for the management of gastric- acid related diseases. The aim of this study was to assess the trend of PPIs uses among the pharmaceutical promotional workers in Bangladesh. Methods: A questionnaire-based survey was conducted on pharmaceutical promotional workers from different regions in Bangladesh. The study data were collected which includes demographics, PPIs uses in terms of duration, dose, generics, symptoms for which they took PPIs and effects of PPIs on symptoms. Drugs or diseases that influenced the intake of PPIs were also recorded. Results: Among six hundred surveys issued for the study, 581 valid questionnaires were returned. Among the respondents 520 individuals (89.5%) were male and 61 individuals (10.5%) were female. Common indications for taking PPIs were abdominal discomfort (51.5%), vomiting (34.1%) and abdominal pain (24.6%). Two hundred seventy (48.56%) respondents had satisfactory relief of symptoms, 125 (22.48%) had symptoms reappeared after stopping PPIs and 77 (13.85%) had complete cure of symptoms. Most of the participants (42.60%) were on PPIs therapy for up to one year. Most of the participants (64.49%) took PPI once daily. Most of the participants (60.75%) started PPI by themselves. Esomeprazole (40.1%) and rabeprazole (30.1%) were the most frequently used PPIs. Conclusion: PPI is found to be a frequently used medication among pharmaceutical promotional workers. Further well-designed study with adequate work up may be designed to see misuse and overuse of PPI among workers of pharmaceutical sector as well as general population. Sir Salimullah Med Coll J 2023; 31: 41-46